The Influence of Visitor Satisfaction on Hotel Customer Loyalty - Jannah, Annita (Jurnal Bisnis Mahasiswa, 2024)
The reduction in visitors to accommodation or hotels is certainly due to several factors, both external and internal hotel factors. This could include customers being dissatisfied with the results of their visit, so they no longer want to visit the hotel. Therefore, this research will test whether customer dissatisfaction affects hotel visitor loyalty. The data collection method uses verification and descriptive methods. The research results show that customer satisfaction is generally quite high to very high. In this customer satisfaction variable, system satisfaction is the largest, and company satisfaction is the smallest. The biggest aspect is that the hotel can evaluate the benefits obtained by customers, and the statement that customers are satisfied with good and fast customer behavior the smallest aspect is that the hotel is less able to establish quality relationships and in the statement, it lacks a high commitment to cooperation with customers.